2022
DOI: 10.3390/ijms23020640
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Jaws in Patients with Hereditary Thrombophilia/Hypofibrinolysis—From Pathophysiology to Therapeutic Implications

Abstract: Osteonecrosis of the jaws (ONJ) usually has a clear etiology. Local infection or trauma, radiotherapy and drugs that disrupt the vascular supply or bone turnover in the jaws are its major contributors. The thrombotic occlusion of the bone’s venous outflow that occurs in individuals with hereditary thrombophilia and/or hypofibrinolysis has a less known impact on jaw health and healing capability. Our research provides the most comprehensive, up-to-date and systematized information on the prevalence and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 185 publications
0
5
0
Order By: Relevance
“…Moreover, radiation therapy to organs other than the jawbone is often administered to such cancer patients, and the risk factors are thus inevitably increased. Chemotherapy, such as BMA, suppresses bone metabolism and causes immune changes; hence, it is also considered a risk factor for ARONJ [ 14 , 15 , 16 ]. This study showed that breast cancer, radiation therapy, and chemotherapy factors were more strongly correlated with ARONJ onset than were other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, radiation therapy to organs other than the jawbone is often administered to such cancer patients, and the risk factors are thus inevitably increased. Chemotherapy, such as BMA, suppresses bone metabolism and causes immune changes; hence, it is also considered a risk factor for ARONJ [ 14 , 15 , 16 ]. This study showed that breast cancer, radiation therapy, and chemotherapy factors were more strongly correlated with ARONJ onset than were other factors.…”
Section: Discussionmentioning
confidence: 99%
“…During the drug holiday, BP remains in the bone because it is incorporated into the calcified bone matrix, and bone clearance can range from weeks to years. Therefore, the drug holiday of BP is expected to have limited or no effect on bone turnover [ 15 , 17 , 18 ]. Meanwhile, nitrogen-containing BPs promote bacterial adhesion and biofilm formation, which can cause ARONJ by angiogenesis suppression and soft-tissue toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR and PLR are systemic markers of overall inflammation [ 13 , 14 ]. Inflammation, procoagulant imbalance, and endothelial dysfunction play important roles in the development of osteonecrosis of the jaw and its complications [ 15 ]. Inflammatory disorders often cause tissue damage, severe pain, and jaw dysfunction in patients with ARONJ [ 16 , 17 ] and often require hospitalization for inflammation of ARONJ.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate fibrinolysis and excessive thrombophilia are the primary causes of this. Both acquired and hereditary thrombophilia/hypofibrinolysis can result in osteonecrosis of the femoral head and jaw at all ages [ 46 , 47 ]. Extreme thrombophilia, also known as hypercoagulability, is a coagulation disorder in which a great number of blood clots form on the walls of circulating blood vessels.…”
Section: Endothelial Dysfunction Promotes Coagulopathymentioning
confidence: 99%